Topographic separation of fornical fibers associated with the anterior and posterior hippocampus in the human brain: An MRI‐diffusion study. Issue 1 (22nd November 2016) - Christiansen, Kat; Metzler‐Baddeley, Claudia; Parker, Greg D.; Muhlert, Nils; Jones, Derek K.; Aggleton, John P.; Vann, Seralynne D.
Abstract: Background and Objective: Evidence from rat and nonhuman primate studies indicates that axons comprising the fornix have a characteristic topographical organization: projections from the temporal/anterior hippocampus mainly occupy the lateral fornix, whereas the more medial fornix contains fibers from the septal/posterior hippocampus. The aim of this study was to investigate whether the same topographical organization exists in the human brain. Methods: Using high angular resolution diffusion MRI‐based tractography at 3T, subdivisions of the fornix were reconstructed in 40 healthy adults by selecting fiber pathways from either the anterior or the posterior hippocampus. Results: The tract reconstructions revealed that anterior hippocampal fibers predominantly comprise the lateral body of the fornix, whereas posterior fibers make up the medial body of the fornix. Quantitative analyses support this medial:lateral distinction in humans, which matches the topographical organization of the fornix in other primates. Conclusion: This novel tractography protocol enables the separation of fornix fibers from anterior and posterior hippocampal regions in the human brain and, hence, provides a means by which to compare functions associated with different sets of connections along the longitudinal axis of the hippocampus. Abstract : Diffusion MR imaging was used to reconstruct the fornix according to connections with the anterior and posterior hippocampus. A clear distinction with anterior hippocampal fibers located laterally within the fornix and posterior hippocampal fibers located medial was found, consistent with what is currently known about fornix topography in the nonhuman primate. Our method provides a novel way to investigate functional dissociations along the long axis of the hippocampus.